2017
DOI: 10.9744/jak.19.1.24-36
|View full text |Cite
|
Sign up to set email alerts
|

Board Structures dan Value-Added Intellectual Capital: Studi Kasus pada Industri Barang Konsumsi dan Perdagangan Indonesia

Abstract: ABSTRAK

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
2
1
0
Order By: Relevance
“…In addition, empirical evidence shows that the larger the firm size, the more the IC disclosure was made in manufacturing firms. This discovery complies with [39]- [41].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, empirical evidence shows that the larger the firm size, the more the IC disclosure was made in manufacturing firms. This discovery complies with [39]- [41].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, studies by the following Europeans, [20], [37] and [38], concluded it had a positive influence on IC disclosure. Similar studies conducted in Indonesia and by [39]- [41] equally supported this claim. Therefore, the first hypothesis proposed in this research is that firm size has a positive influence on IC Disclosure.…”
Section: E Hypothesis Development 1) the Influence Of Firm Size On Ic Disclosuresupporting
confidence: 84%
“…Several empirical studies have tried measuring the factors that affect the creation of intellectual capital in an organization; whether in the shape of value-added capital as suggested by Pulic in 1998(Al-Musali & Ismail, 2015Appuhami & Bhuyan, 2015;Hatane et al, 2017;Nadeem et al, 2017) or as the disclosure of intellectual capital activities (Ousama et al, 2012;Mondal & Ghosh, 2014;Morariu, 2014;Abhayawansah & Azim, 2014;Kamath, 2017). This has become a challenge for further researchers who want to expand on the topic of intellectual capital.…”
Section: Introductionmentioning
confidence: 99%